Patients’ trust in healthcare providers and associated factors among hospitalized patients in Awi Zone Public Hospitals, Northwest Ethiopia - Baymot Bitew Bekele; Kelemework Gashinet Ferede; Abebaw Bires Adal; Addisu Gasheneit Ferede; Atsedemariam Andualem; Desalegn Yeshalem Mitiku; Aragaw Egziabherfenta Tadele; Asrat Yazew; Birhaneslasie Gebeyehu Yazew (PLoS ONE, 2026)
Background Trust in healthcare providers (HCPs) is crucial for increasing health-seeking behavior, strengthening patient-provider relationships, and improving clinical outcomes. While vital, research on patient trust in HCPs remains limited in the Ethiopian context. This study assessed the level of trust and its associated factors among hospitalized patient in Awi Zone public hospitals, Northwest Ethiopia. Methods An institution-based cross-sectional study was conducted from June 05 to September 30, 2024. The sampling frame consisted of all adult patients admitted to the medical, surgical, and gynecological wards of five public hospitals. A total of 621 participants were selected using simple random sampling from the daily admission logs. Data were collected via a pretested, interviewer-administered questionnaire. EpiData 4.6 and SPSS version 25 were used for data entry and analysis respectively. Logistic regressions were applied to identify factors associated with patient trust. Associations were considered significant at p value < 0.05. Trust was measured using a validated scale, where “high trust” was operationally defined as a score $\ge$ 32 (based on the mean score of the study population). Bivariable and multivariable logistic regressions were used to identify factors associated with trust, with significance set at $p < 0.05$. Results The study achieved a 96% response rate (n = 621). Overall, 47.3% of patients reported high trust in HCPs (95% CI: 43.4–51.4). Factors significantly associated with higher trust included: rural residence (AOR = 2.44; 95% CI: 1.27–4.69), absence of comorbidity (AOR = 1.75; 95% CI: 1.15–2.65), not having health insurance (AOR = 1.53; 95% CI: 1.09–2.14), and a hospital stay of less than 29 days (AOR = 1.89; 1.12–3.20). Conclusion Fewer than half of hospitalized adults expressed high trust in HCPs. To bridge this gap, hospital management should implement mandatory patient-centered communication training for clinicians and establish dedicated support protocols for patients with chronic comorbidities. Furthermore, improving the transparency of insurance billing and discharge processes is essential for urban and long-term patients.